Effects of aquatic exercise on mood and anxiety symptoms: A systematic review and meta-analysis - Tang, Zhengyan; Wang, Ye; Liu, Jingmin; Liu, Yujie (Frontiers in Psychiatry, 2022)
Objective: Exercise have beneficial effects to mood and anxiety symptoms. There was no sufficient evidence to recommend that aquatic exercise was potentially beneficial to mood and anxiety symptoms. The aim of this study was to systematically analyze all evidence available in the literature on the promotion of mental health of the aquatic exercise. Method: A scoping review was performed under the PRISMA 2020 guidelines. PubMed, BIOSIS Previews, Psycinfo, Medline, SPORTDiscus, Education source and Web of science core collection were searched in May, 2022 was conducted. Studies include the effect of aquatic exercises on mental health. With document quality evaluations and data extraction, Meta-Analysis was performed using a random effect model. The results were expressed in terms of standardized mean difference and the corresponding 95% confidence interval. Results: A total of 18 original studies were included. People who were intervened with aquatic exercise showed a statistically significant reduction in mental disorder symptoms compared pro-intervention. The results were: aquatic exercise [SMD = –0.77, 95% CI (–1.08, -0.47), I2 = 77%, P < 0.01]; swim [SMD = –0.51, 95% CI (–1.14, 0.12), I2 = 78%, P < 0.01] ; aquatic aerobics [SMD = –0.92, 95% CI (–1.32, –0.53), I2 = 78%, P < 0.01]; moderate intensity [SMD = –0.75, 95% CI (–1.07, -0.43), I2 = 67%, P < 0.01] and light intensity [SMD = –1.07, 95% CI (–1.08, –0.47), I2 = 85%, P < 0.01]. Conclusion: Aquatic exercise could statistically significantly improve mental health. Light aquatic aerobics may have a better effect on mood and anxiety symptoms. However, limited by the number and quality of included studies, the above conclusions need more large sample high-quality studies to verify.